Emotional and Cognitive Responses to Theatrical Representations of Aggressive Behavior - Berceanu, Alexandru I.; Matu, Silviu; Macavei, Bianca I. (Frontiers in Psychology, 2020)
Representation of human conflict is central to theatre performance. In our study we have used self-reported measures of emotional experience and a word recall task, in order to assess the effects of theatrical representations of violence. Forty participants were randomly assigned to the role of performer or spectator, in either a realistic representation of a script, or in a version that recollected the same actions of the script in a series of intertwined monologues. The script represented an aggressive interaction between two work colleagues. Our results show both statistically significant differences in the levels of depression and positive emotions reported after enacting the script, as well as differences in the performance on the word recall task containing aggressive related and non-related stimuli. The results point to stronger effects for performing theatrical representations of violent actions, as compared to recollecting or watching such actions. The fact that actors experienced higher positive emotions is in line with the two-pedal model of aggressive behavior. This model suggests that negative emotions toward aggressive behavior might change to positive emotions due to the repetition in performing violent behaviors, as a key for the transition from reactive aggression to appetitive aggression. Other implications for the study of aggression in theatrical representations are discussed.